Pengaruh Model Pembelajaran Kelompok (Cooperative Learning) Terhadap Perkembangan Sosial Emosional Anak Usia 5-6 Tahun Di RA Plus Fatahul Wardah Palembang - Fadhilah, Jihan; Mardeli, Mardeli; Fitri, Izza (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the effect of the cooperative learning model on the social-emotional development of children aged 5-6 years at RA Plus Fatahul Wardah Palembang. The research method used is quantitative with an experimental approach. The research sample consisted of 12 children selected randomly. Data collection was conducted through pretests and posttests using appropriate instruments. The results of the study showed a significant improvement in children's social-emotional development after implementing the cooperative learning model. In the pretest, the average score obtained was 39.33, while after treatment (posttest), it increased to 78.8. Hypothesis testing indicated that tcount = 26.32638 was greater than ttable = 2.228139, leading to the acceptance of Ha and the rejection of Ho. Thus, it can be concluded that the cooperative learning model significantly influences the social-emotional development of children aged 5-6 years. The indicators that showed improvement include teamwork skills, emotional regulation, self-confidence, and communication abilities.